Smart postharvest management of horticultural crops through digital solutions - P., Suresh Kumar; T., Shuprajhaa (Indian Horticulture, 2025)
Digital tools such as sensors, Internet of Things (IoT) devices, blockchain, and data analytics offer effective solutions to several challenges, ensuring crops maintain their quality and freshness throughout the supply chain. IoT-based cold chain solutions are gaining importance in India. These systems alert farmers and distributors when conditions are not optimal, helping reduce spoilage during storage and transit. Data-driven insights that assist farmers in making informed decisions about harvest timing, storage, and market prices offers solution for profitability and sustainability. By using satellite imagery, weather data, and predictive analytics, it is possible to optimize postharvest management practices, helping reduce losses and improve profitability for Indian farmers. In food processing, digital technologies are also transforming operations. Automated systems with IoT sensors and AI algorithms enhance efficiency and quality. Blockchain technology is another vital tool being explored to enhance traceability in India’s supply chain and provide end-to-end traceability, ensuring that both domestic and international consumers receive high-quality produce. This is particularly valuable for exports, which must meet strict quality and safety standards.